Istilah dalam Permainan Bekelan di Kota Surakarta: Kajian Antropolinguistik - Amelia Fatimah; Suyanto Suyanto; Sri Puji Astuti (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
Language variations relate to different cultures. The relationship between language and culture is found in terms of traditional game, that’s bekelan. Bekelan is a game that’s played by several people in turns using ball and objects called kecik. The game is rarely played by children, so it needs to be preserved. This study aims to explain the lexical meaning, cultural meaning, co-text, and cultural values of bekelan’s terms in Surakarta. The theory used in the study is anthropolinguistic. Data were collected using interview techniques and literature study. Bekelan in Surakarta has fourteen terms, they are name, tools, and rules of the game. The data were analyzed using ethnographic descriptive. The result of data analyisis are presented using formal and informal methods. The result based on the data analysis found that bekelan’s terms have (1) lexical meanings and cultural meanings, (2) co-texts are material and kinetic elements, and (3) cultural values are values of human relationship with God, human relationship with nature, human relationship with society, human relationship with other humans, and human relationship with hisself.